2022
DOI: 10.1063/5.0087838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonally forced noisy environment on aquatic prey–predator model with water level fluctuations

Abstract: In this paper, the impact of environmental noise on prey–predator interactions with seasonal fluctuations in water levels has been studied. Both intensity of noise and water level variations together play a significant role in the dynamics of an aquatic prey–predator system. Analytically, we have shown the existence of a positive solution and its uniqueness, the ultimate bound of the system’s solutions, and the global attractivity of the solution. Moreover, parametric conditions for which model species either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Investigations on fear‐induced prey–predator systems with stochastic environments revealed that under lower environmental disturbances, model species fluctuate around average deterministic steady‐state values, while higher disturbances lead to species extinction [17]. Research assessing the impact of environmental noise on prey–predator interactions with seasonal water level fluctuations highlighted the significant roles played by noise intensity and water level variations in aquatic systems [22]. In a recent study exploring a predator–prey system within a stochastic environment featuring a modified Holling type II functional response, harvesting, and the Allee effect, the stochastic nature of the system unveiled various transitions, particularly notable in scenarios with heightened noise intensity [23].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on fear‐induced prey–predator systems with stochastic environments revealed that under lower environmental disturbances, model species fluctuate around average deterministic steady‐state values, while higher disturbances lead to species extinction [17]. Research assessing the impact of environmental noise on prey–predator interactions with seasonal water level fluctuations highlighted the significant roles played by noise intensity and water level variations in aquatic systems [22]. In a recent study exploring a predator–prey system within a stochastic environment featuring a modified Holling type II functional response, harvesting, and the Allee effect, the stochastic nature of the system unveiled various transitions, particularly notable in scenarios with heightened noise intensity [23].…”
Section: Introductionmentioning
confidence: 99%